Canadian Arctic Neogene Temperatures Reconstructed From Hydrogen Isotopes of Lignin‐Methoxy Groups From Sub‐Fossil Wood. Issue 2 (27th January 2022) - Porter, Trevor J.; Anhäuser, Tobias; Halfar, Jochen; Keppler, Frank; Csank, Adam Z.; Williams, Christopher J.
Abstract: Proxy‐based reconstructions of Neogene warm climates are a valuable data source for helping to understand what a future, warmer world may look like. Such insights are especially critical in the Arctic where the fastest rates of warming are underway and likely to continue. In this study, hydrogen isotopes of lignin‐methoxy groups (δ 2 HLM ) from Miocene and Pliocene sub‐fossil wood samples ( N  = 43) at six high‐latitude sites (73–80°N) in the Canadian Arctic Archipelago were used to estimate mean δ 2 H values of precipitation and temperature anomalies (ΔT) relative to present. The ΔT estimates ranged from +9.7 to +16.7°C depending on site and epoch and are corroborated by a suite of independent proxy data for most sites, and for one site (Prince Patrick Island) this study provides the first quantitative ΔT estimates. These are conservative estimates as they do not account for the more negative δ 2 Hseawater values during the Neogene. These ΔT estimates, along with independent proxy and vegetation data, depict a dramatically warmer version of the Arctic. Some of this warming was likely driven by global atmospheric change and feedbacks that are possible in the modern‐day Arctic. However, transformation of the once‐contiguous Arctic landmass into a dissected archipelago has undoubtedly changed the nature and future warming potential of the Canadian Arctic region. Investigations aimed at disentangling the relative contribution of global versus regional boundary conditions to Neogene Arctic climate warming are needed to understand the extent to which these reconstructions may foreshadow conditions in the future. Key Points: Miocene and Pliocene paleotemperatures were reconstructed for Canadian Arctic sites using δ 2 Hlignin‐methoxy values of sub‐fossil wood Depending on site/epoch, reconstructed temperatures were 9.7–16.7°C warmer than today and are corroborated by independent proxies These findings refine our knowledge of Neogene warming in the Canadian Arctic and of the processes driving this warming